The Dionysian Ancient Reliefs of the Cardelli Collection: A Product of Seventeenth Century Classicism or an Interpretative Paradigm? .......... 347 - Cursi, Giulia Moretti (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
The paper aims to consider Cardelli collection of antiquities as a minor example pertaining to a mechanism of emulation and social ascent of the great 17th-century collections of antiquities in Rome. With this mind, we can see the reflection of the debate between the two opposite ideals of iudicium and ingenium. The oscillation between these two poles of philological practice is reflected on what has been defined by I. Faldi as the “mystification of the ancient.” One of the major representatives of this new stream was Orfeo Boselli, a pupil of Cristoforo Stati and François Duquesnoy, who restored the Dionysian reliefs preserved in the Cardelli palace in Rome. Accordingly, both ancient and pseudo antique works will be presented along the transcription of archival texts from the Cardelli Archive kept in the Capitoline Historical Archive in Rome that are relevant to the acquisition, cataloguing, and restoration of the objects.